High-Intensity Interval Training Attenuates Ketogenic Diet-Induced Liver Fibrosis in Type 2 Diabetic Mice by Ameliorating TGF-β1/Smad Signaling - Zhang Q (Dove Medical Press, 2020)
Qiang Zhang,1,2,* Fei Shen,1,2,* WenQing Shen,1,2 Jie Xia,1,2 Jing Wang,1,2 Yu Zhao,1,3 Zhe Zhang,1,2 Yi Sun,1,2 Min Qian,4 ShuZhe Ding1,2 1Key Laboratory of Adolescent Health Assessment and Exercise Intervention of Ministry of Education, East China Normal University, Shanghai 200241, People’s Republic of China; 2School of Physical Education & Health, East China Normal University, Shanghai 200241, People’s Republic of China; 3Center for Physical Education, Xi’an Jiaotong University, Xi’an, Shaanxi 710049, People’s Republic of China; 4Shanghai Key Laboratory of Regulatory Biology, Institute of Biomedical Sciences and School of Life Sciences, East China Normal University, Shanghai 200241, People’s Republic of China*These authors contributed equally to this workCorrespondence: ShuZhe Ding Tel +86 13601798505Email szding@tyxx.ecnu.edu.cnObjective: Ketogenic diet (KD) and high-intensity interval training (HIIT) have preclinical benefits for type 2 diabetes (Db). However, the health risks of long-term KD use in diabetes should be ascertained and prevented. We hypothesized that KD-induced liver fibrosis in type 2 diabetic mice could be ameliorated by HIIT.Methods: Streptozotocin-induced type 2 diabetic mice were divided into high-fat diet (HFD) control (Db+HFD+Sed), KD control (Db+KD+Sed), HFD coupled with HIIT (Db+HFD+HIIT), and KD coupled with HIIT (Db+KD+HIIT) groups (n=6, per group). Control mice were kept in sedentary (Sed), while HIIT group mice underwent 40-minute high-intensity interval training three alternate days per week. After 8-week intervention, the indicators of body weight and insulin resistance, oxidative stress markers, hepatic fibrosis, genetic and protein expression of related pathways were tested.Results: We found that fasting blood glucose level was reduced in the Db+HFD+HIIT, Db+KD+Sed, and Db+KD+HIIT groups. Insulin sensitivity was increased in diabetic mice of these groups, whereas ROS levels were decreased in mice that underwent HIIT. The immunohistochemical staining of liver, serum index, and hepatic parameters of diabetic mice in the KD group revealed liver fibrosis, which was significantly attenuated by HIIT. Besides, these effects of HIIT were the outcome of hepatic stellate cell’s inactivation, reduced protein expression of matrix metalloproteinases and tissue inhibitor of metalloproteinases, and the inhibition of TGF-β 1/Smad signaling.Conclusion: KD had a profound fibrotic effect on the liver of type 2 diabetic mice, whereas HIIT ameliorated this effect. KD did not show any apparent benefit as far as glucose tolerance and homeostasis were concerned. Concisely, our results demonstrated that KD should be coupled with HIIT for the prevention and preclinical mitigation of type 2 diabetes.Keywords: diabetes, ketogenic diet, high-intensity interval training, hepatic fibrosis, ROS, TGF-β 1/Smad signal